2002
DOI: 10.1016/s0967-067x(01)00022-8
|View full text |Cite
|
Sign up to set email alerts
|

Party support or personal resources? Factors of success in the plurality portion of the 1999 national legislative elections in Russia

Abstract: The paper estimates party-related and non-party-related factors of electoral success in single-member district elections to the Russian State Duma in December 1999. As demonstrated by the analysis, both kinds of factors facilitate candidates’ performance, but the utility of personal political resources of non-electoral origins is greater than that of party support. Thus it is likely to be valued by Russian politicians as a supplement, not as a core component of their electoral strategies. By distorting the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In some less established systems, such as Russia and the Ukraine, research has suggested that the number of successful independent candidates indicates how politicians can be electorally viable without partisan affiliation (Birch, 1998;Golosov, 2002;Moser, 1999). A more substantial impediment to party development is the influence of other key groups.…”
Section: Institutionalization In the Post-communist Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In some less established systems, such as Russia and the Ukraine, research has suggested that the number of successful independent candidates indicates how politicians can be electorally viable without partisan affiliation (Birch, 1998;Golosov, 2002;Moser, 1999). A more substantial impediment to party development is the influence of other key groups.…”
Section: Institutionalization In the Post-communist Contextmentioning
confidence: 99%
“…On the other hand, while parties are important for reducing the costs of organization and mobilization of voters, in less established systems this is not always the case. In some less established systems, such as Russia and the Ukraine, research has suggested that the number of successful independent candidates indicates how politicians can be electorally viable without partisan affiliation (Birch, 1998;Golosov, 2002;Moser, 1999). A more substantial impediment to party development is the influence of other key groups.…”
Section: Institutionalization In the Post-communist Contextmentioning
confidence: 99%
“…Third, it is not clear that transfers would make a huge difference in SMD elections. Previous analyses of successful SMD candidates indicate that personal resources (incumbency, business ties, experience in regional politics) were key, as was support from regional governors (Golosov, ; Myagkov and Ordeshook, ). In the former case, supplementary resources from the center would likely be marginal at best, even if well targeted.…”
Section: Modeling Strategic Transfersmentioning
confidence: 99%
“…This seems to be the case in Russia, with its long history of rather competitive elections. Even if not structured along party lines, these elections witnessed vigorous contestation among subnational elites both in national elections (Golosov 2002) and at the regional level (Golosov 2004). In addition, party building under authoritarianism necessarily involves overcoming the commitment problem of sub-national elites, which makes it imperative for them to invest their resources in the dominant party (Reuter and Remington 2008).…”
Section: Theoretically and Empirically Informed Expectationsmentioning
confidence: 99%